2019
DOI: 10.1186/s41182-019-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factor RNA transcript expression in the Leishmania Viannia subgenus: influence of species, isolate source, and Leishmania RNA virus-1

Abstract: Background Leishmania RNA virus-1 (LRV1) is a double-stranded RNA virus identified in 20–25% of Viannia —species endemic to Latin America, and is believed to accelerate cutaneous to mucosal leishmaniasis over time. Our objective was to quantify known virulence factor (VF) RNA transcript expression according to LRV1 status, causative species, and isolate source. Methods Eight cultured isolates of Leishmania … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…Since L. infantum-induced visceral form, (the most invasive leishmaniasis) and L. major induce a more devastating form of CL compared to L. tropica, the higher level of CPB expression is expected in these species. Moreover, in agreement with our findings, a study by Kariyawasam et al [27] revealed that pooled virulence factors transcript was lower in L. (V.) panamensis isolates than that of L.(V.) braziliensis and L. (V.) guyananesis at 24 h post macrophage infection, which might reflect that a strain of L. (V.) panamensis originated from a patient with non-severe CL while L. (V.) braziliensis isolates derived from more clinically invasive lesions. These findings suggested the most expression of virulence factors could be exhibited in the species inducing more severe clinical forms [27,28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Since L. infantum-induced visceral form, (the most invasive leishmaniasis) and L. major induce a more devastating form of CL compared to L. tropica, the higher level of CPB expression is expected in these species. Moreover, in agreement with our findings, a study by Kariyawasam et al [27] revealed that pooled virulence factors transcript was lower in L. (V.) panamensis isolates than that of L.(V.) braziliensis and L. (V.) guyananesis at 24 h post macrophage infection, which might reflect that a strain of L. (V.) panamensis originated from a patient with non-severe CL while L. (V.) braziliensis isolates derived from more clinically invasive lesions. These findings suggested the most expression of virulence factors could be exhibited in the species inducing more severe clinical forms [27,28].…”
Section: Discussionsupporting
confidence: 94%
“…In this context, a correlation between the CPB expression and virulence has been reported in L. amazonensis promastigotes [29]. Also, the highest expression of CPB was reported in L. (V.) braziliensis isolates derived from more clinically invasive lesions in comparison with a strain of L. (V.) panamensis originated from a patient with non-severe CL, suggesting an association of clinical phenotype and expression level of virulence factors [27]. Likewise, our findings suggest a probable correlation between the duration of wound and CPB gene expression; however, since the progression of wound is multifactorial further analysis is needed to confirm it.…”
Section: Discussionmentioning
confidence: 90%
“…equipped with RNA interference machinery (the system allowing the cell to actively recognize and degrade non-self dsRNA, likely to be mainly of viral origin) suggesting the importance of the parasite’s anti-viral defense in finely balancing viral replication rate [ 87 ]. Differently from TVV, the presence of LRV does not affect parasite growth and there is no evidence of modulation of parasite gene expression [ 88 ]. Despite LRV has been isolated from active and healing lesions and scars [ 89 91 ], thus far no experimental system has allowed long-term maintenance of LRV in Leishmania following experimental transfer (N. Fasel personal communication).…”
Section: Main Textmentioning
confidence: 99%
“…Virulence factors are considered potential drug targets and vaccine candidates for controlling leishmaniasis [12]. Cysteine proteinases (CPs) are immunogenic proteins and include cysteine protease types I-III (CPB, CPA, and CPC, respectively).…”
Section: Introductionmentioning
confidence: 99%